Against Violence Against Women - Fields, R. author. aut Link
XI, 220 p.
Keywords: Responding to the targeted destruction of women, Fields argues for establishing Gender as a protected class under the Genocide Convention. Cases are explored, historically, anthropologically, psychologically and sociologically, from the author's field research, as well as focuses on morbidity, mortality and demographic documentation data.